(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Teaching trigonometry in academic lyceums presents unique challenges due to the abstract nature of the subject and its critical role in higher mathematics. This paper explores effective pedagogical strategies to enhance the understanding and engagement of students in trigonometric topics. By focusing on interactive methodologies, real-world applications, and digital resources, the study aims to provide educators with practical tools to foster deeper comprehension and retention. Special attention is given to the context of Uzbekistan’s academic lyceum system, aligning teaching methods with national educational standards and technological advancements.